Irregularities in a metal-dielectric shielded waveguide with low losses for the frequency range 90–100 GHz - Vladislav V. Krutskikh; Andrey N. Ushkov; Husam Ariqat; Denis O. Zavitaev; Artavazd E. Mirzoyan (Физика волновых процессов и радиотехнические системы, 2022)
This article is devoted to the study of waveguide metal-dielectric structures in the frequency range of 90100 GHz with low losses up to 0,05 dB/m. The paper considers the effect of sharp irregularities on a section of a regular line, which leads to a change in the parameters of a metal-dielectric closed waveguide path. In practice, irregularities have a negative impact on the transfer characteristic of the waveguide. Therefore, the types of irregularities often found in modern devices were investigated. As a result of the analysis of the losses caused by the rupture of the dielectric rod and the rotation of the polarization plane, the approximated characteristics of the transfer function of the waveguide line with irregularity were obtained.